The first representatives of velvety and sclerotioid polypores with rhizomorphs of a newly-recorded genera in national park of Cat Tien, south Vietnam: Lignosus sacer (Fr.) Ryv. & Laccocephalum hartmannii (Cooke) Nunez & Ryv. - Tham, Le Xuan (Academia Journal of Biology, 2014)
1. The first representative of sclerotioid polypores with rhizomorphs of a newly-recorded genus in Vietnam - Type species Lignosus sacer (Fr.) Ryv. was recorded to enlarge it’ distribution from tropical Africa (Sierra Leone to Kenya) to South Africa to South East Asia. Morphological characters of Lignosus sacer (Fr.) Ryv. are quite similar to L. rhinocerus (Cooke) Ryv., which is commonly found in Asia, from Sri Lanka, Malay Peninsula, Indonesia, Borneo, The Phillippines, New Guinea and Australia, but Lignosus sacer (Fr.) Ryv. differs in having light brown upper surface of the pilei and larger pores and apparently larger spores, and without grey shades on the pilei. 2. A polypore with bay velvety stipe was collected in National Park of Cattien, South Vietnam and identified as the first representative of a newly-recorded genus: Laccocephalum hartmannii (Cooke) Nunez & Ryv., com. nov. (basionym as Polyporus hartmannii Cooke). The sophisticated descriptions and illustrations with authentic specimens from nature in rainy seasons (July 2005, September 2006) were presented without pseudosclerotia. The distribution of this species was expanded from Tasmania, Australia (1883) to Japan (1995) and South Vietnam (2005). These genera, in fact, were derived and isolated from Polyporus Fr. according to taxonomy revision by Ryvarden & Nunez to circumscribe Polyporus s.s. Ryvarden (1995) and show their differenciations in South East Asia regions.